LC-MS/MS를 이용한 수산물 중 니트로빈의 정량분석법 개발 및 검증 - 김주혜; 신다솜; 강희승; 정지윤; 이규식; Kim, Joohye; Shin, Dasom; Kang, Hui-Seung; Jeong, Jiyoon; Rhee, Gyu-Seek (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2018)
The objective of this study was to develop a sensitive method for the identification and determination of nitrovin in fishery products by using a solid-phase extraction (SPE), as performed with a liquid chromatography-tandem mass spectrometry (LC-MS/MS). The samples were extracted with a mixture of acetonitrile and water, and were then defatted with acetonitrile saturated hexane, after which further clean-up was accomplished with SPE on the hydrophilic-lipophilic balance (HLB) cartridges. The analytes were subsequently ionized in the positive mode of an electrospray ionization (ESI), and where thereby detected in a process of multiple reaction monitoring (MRM). The linearity (expressed as correlation coefficients) of the matrix calibration curves was > 0.985. The limit of the quantification for the nitrovin was measured at 0.001 mg/kg. The accuracy (expressed as average recovery) was noted between 72.1 and 122%. The precision (expressed as coefficient variation) was noted from 2.9 to 16.9%. According to the CODEX CAC/GL-71 guideline accuracy, precision, linearity, and limit of detection were determined in three matrices (which were flatfish, eel and shrimp). The proposed method was suitable for analyzing the associated nitrovin residues. This application and result can also be a factor to contribute to the non-detection drugs management in fishery products. 본 연구에서는 우리나라 식품공전에서 불검출 물질로 관리하고 있는 니트로빈(nitrovin)에 대해 고감도 정량 정성분석이 가능한 LC-MS/MS를 적용하여 적합한 분석법을 제시하고자 하였다. 수산물 시료는 아세토니트릴/물로 추출하고 아세토니트릴 포화 헥산으로 지방을 제거하여 고상추출 카트리지를 적용하여 정제하였다. 분석물질은 전기분무이온화방법의 positive mode에서 이온화하여 MRM 조건을 확립하여 분석하였다. 개선된 시험법은 CODEX CAC/GL-71 가이드라인에 따라서 정확성, 정밀성, 직선성, 정량한계에 대한 검증을 통하여 유효성을 확인하였다. 본 실험에서의 정량한계는 0.001 mg/kg 수준이며, 정량한계를 포함하는 표준시료에서 얻어진 검량선의 상관계수($r^2$)는 0.985 이상으로 시험법의 직선성이 유효함을 판단할 수 있었다. 또한, 수산물(넙치, 장어 및 새우) 시료에 대한 니트로빈의 평균 회수율과 변동 계수는 72.1~122%, 2.9~16.9%로 확인되어 정확성 및 정밀성이 CODEX가이드라인에 부합하였다. 따라서, 개선된 니트로빈 정량분석법은 수산물 중 니트로빈을 분석하는데 적합하며, 니트로빈에 대한 지속적인 잔류실태조사에 활용되어 수산물 중 니트로빈의 안전관리에 기여할 것으로 판단된다.